2013
DOI: 10.1021/nl400579g
|View full text |Cite
|
Sign up to set email alerts
|

Engineering the Thermopower of C60 Molecular Junctions

Abstract: We report the measurement of conductance and thermopower of C60 molecular junctions using a scanning tunneling microscope (STM). In contrast to previous measurements, we use the imaging capability of the STM to determine precisely the number of molecules in the junction and measure thermopower and conductance continuously and simultaneously during formation and breaking of the molecular junction, achieving a complete characterization at the single-molecule level. We find that the thermopower of C60 dimers form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
205
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 161 publications
(222 citation statements)
references
References 18 publications
15
205
2
Order By: Relevance
“…These values are close to the experimental values found in Ref. 34, where mean values of 0.1G 0 and 1.8 × 10 −3 G 0 were reported for the monomer and dimer junctions, respectively. Notice that in both cases the electronic transmission at the Fermi energy is determined by the LUMO of the molecules, as it has been reported in numerous studies, see for instance Ref.…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…These values are close to the experimental values found in Ref. 34, where mean values of 0.1G 0 and 1.8 × 10 −3 G 0 were reported for the monomer and dimer junctions, respectively. Notice that in both cases the electronic transmission at the Fermi energy is determined by the LUMO of the molecules, as it has been reported in numerous studies, see for instance Ref.…”
Section: Resultssupporting
confidence: 92%
“…Notice also that the thermopower value for the dimer junction almost doubles that of the monomer, similar to what was observed in Ref. 34, while the absolute values are somewhat larger than those reported experimentally.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…S tudies of the electrical conductance of single molecules attached to metallic electrodes not only probe the fundamentals of quantum transport but also provide the knowledge needed to develop future molecular-scale devices and functioning circuits [1][2][3][4][5][6][7][8][9] . Owing to their small size (on the scale of Angstroms) and the large energy gaps (on the scale of eV), transport through single molecules can remain phase coherent even at room temperature, and constructive or destructive quantum interference (QI) can be utilized to manipulate their room temperature electrical 10-13 and thermoelectrical 14,15 properties. In previous studies, it was reported theoretically and experimentally that the conductance of a phenyl ring with meta (m) connectivity is lower than the isomer with para (p) connectivity by several orders of magnitude [16][17][18][19][20][21][22][23][24][25] .…”
mentioning
confidence: 99%